Changes Within Clinical Practice After a Randomized Controlled Trial of Knee Arthroscopy for Osteoarthritis. Issue 4 (10th April 2017) - Amin, Nirav H.; Hussain, Waqas; Ryan, John; Morrison, Shannon; Miniaci, Anthony; Jones, Morgan H.
Background: In 2002, Moseley et al published a randomized controlled trial (RCT) that showed no difference between knee arthroscopy and placebo for patients with osteoarthritis (OA). We wanted to assess the impact of the trial on clinical practice in the United States. Purpose/Hypothesis: To evaluate changes in knee arthroscopy practice before and after publication of the article by Moseley et al and to assess the effect of this landmark RCT on the behavior of practicing orthopaedic surgeons. We hypothesized that after publication of the Moseley trial, the overall frequency of knee arthroscopy would decrease, that the mean age of patients undergoing knee arthroscopy would decrease, and that the proportion of arthroscopies for a diagnosis of OA would decrease. Study Design: Descriptive epidemiology study. Methods: The State Ambulatory Surgery Database was used to analyze cases from 1998 to 2006, which were classified as meniscus tear, OA, or OA with meniscus tear. Changes in age, surgery rates, and case classification were evaluated before and after Moseley's trial using Student t tests and analysis of variance. Results: After publication of the trial, the number of knee arthroscopies per year increased from 155, 057 in 1998 to 172, 317 in 2006 ( P ≤ .001). Mean patient age increased from 47.6 to 49.2 years ( P < .001). Meniscus tears increased from 69.1% to 70.8%, representing approximately 15, 500 additional cases per year. OA decreased from 10.6% to 7.2%, representing approximately 4000 fewer cases per year. OA with meniscus tear increased from 20.3% to 22.0%, representing approximately 6400 additional cases per year. Conclusion: While overall age and rates of knee arthroscopy increased contrary to our hypothesis, we identified a decrease in rates of knee arthroscopy for OA after publication of the Moseley trial, demonstrating that well-publicized RCTs can influence patterns of clinical practice.